Isolation and Characterization of Alkaloids in Peganum Harmala. L Seeds and Detect their Antibacterial Activity against Multidrug-Resistant Acinetobacter Baumanii Bacteria - Zainab J. Qasim (Journal of Global Pharma Technology, 2019)
Objectives: The recent emergence of multidrug resistance (MDR) in Acinetobacter baumannii (A. baumanii) has raised concern in health care settings in Iraq. Peganum harmala  Linn. (P. harmala) is a small genus of Zygophyllaceae family which widely grows widely in Iraq, Middle East, North Africa, Australia and America. One of the important features of P. harmala alkaloids is their bactericidal activity that is comparable with that of common antibiotics, which have many adverse effects. This study aimed to investigate the antimicrobial effect of methanol extract of P. harmala and its derived alkaloids like harmine and harmaline against A. baumanii. Also their synergism activity in combination with synthetic antibiotic was evaluated. In addition, the cytotoxicity of this extract in its derived active compound was evaluated on human lymphocyte. Methods The primary antibacterial activity were assessed using agar well diffusion method for crude extract and total alkaloids. Minimum inhibitory concentration (MIC) and minimum bactericidal concentrations (MBC) were also detected of crude extract, total alkaloids, harmine and harmaline, by using checkerboard method, the present study investigated the combination of harmala seed active compounds with available antibiotics namely: tigecycline, colistin, meropenem, amikacin and levofloxacin against ten of A. baumanii strains. Moreover, the cytotoxicity of methanolic crude extract of P. harmala and its derived alkaloids were studied on human lymphocyte by MTT (thiazolyl blue tetrazolium dye) colorimetric method. Results: For the two tested compounds, methanolic crude extract and total alkaloids within the range of 50 mg/ml to 10 mg/ml concentrations, the total alkaloids exhibited the most potent antibacterial activity against A. baumanii in a dose-dependent manner. the total alkaloids also exhibited the lowest level of MIC and MBC medians 32, 64 μg/ml respectively, whereas harmine and methanolic crude extract showed relatively moderate activity with MIC and MBC medians (96 and 256) (256 and 512) μg/ml respectively, and harmaline had the least inhibitory effect with MIC and MBC median 256 and 768 μg/ml respectively. According to the result of MTT colorimetric method, all concentrations of ≥ 256 μg /ml for harmine, harmaline and total alkaloids and of ≥ 512 μg /ml for methanolic crude extract caused lymphocyte cell death over 50%. For the combinations between harmala seed active compounds and available synthetic antibiotics, the best results were found in the combination between total alkaloids with tigecycline, it was found that 8 out of 10 had synergistic effect (FIC ≤ 0.5) against bacteria while only two had additive effect (FIC= 0.75); combination with colistin showed that only 4 out of 10 had synergistic effect (FIC ≤ 0.5) while 6 out of 10 had additive effect (>0.5-≤1). However, in the combinations with amikacin, meropenem and levofloxacin, all the samples showed indifference effect. Conclusion: Despite the strong antimicrobial effects of high concentrations of P. harmala seeds on A. baumanii, high cell toxicity of this plant would restrict its in vivo therapeutic use. However combination therapy such as the one resulted from synergism between antibiotic and plant extract can be used to minimize the possible toxic effects.Keywords:  Acinetobacter baumanii, Peganum Harmala seeds, Alkaloids, Harmine, Harmaline, antibacterial activity, and synergism.